A study on standard level compliance rate of parathyroid hormone and its correlation with age in elderly patients with peritoneal dialysis - HE Xue-qin; ZHOU Xue-li; JIANG Jing; QIN Min; PU Li; ZHONG Hui (Linchuang shenzangbing zazhi)
Objective To investigate standard level compliance rate of parathyroid hormone(PTH) and its correlation with age in elderly patients with maintenance peritoneal dialysis(PD). Methods The clinical data of 235 patients, who received PD treatment for more than 3 months and regularly followed up in our hospital from January 2011 to January 2012, were collected for a cross-sectional study. According to age, they were divided into elderly group and non-elderly group(≥65 years old and < 65 years old).Blood calcium, blood phosphorus, PTH, other biochemical and nutritional indicators of the two groups were compared, and the correlation between age and PTH was analyzed. Results There was no statistically significant difference in gender composition, height, weight and dialysis age between the two groups(P & GT; 0.05 P> 0.05). Prevalence of diabetes and hypertension was higher in the elderlygroup(P>0.05). The PTH standard level compliance rate in the elderly group was lower than that in the non-elderly group(16.66% vs. 25.66%). The proportion of patients with lower PTH level(<150 pg/mL) was higher in the elderly group than that in the non-elderly group(70.83% vs. 48.66%). The blood phosphorus and serum albumin levels in the elderly group were lower than those in the non-elderly group(P<0.05), and blood calcium and hemoglobin were higher than the non-elderly group(P<0.05). Correlation analysis showed a negative correlation between age and PTH level(R=-0.275, P<0.05). Conclusions The PTH level is correlated with age in PD patients, and is obviously lower in elderly patients, which might result from poor nutritional status and decreased blood phosphorus in elderly patients.